1994
DOI: 10.1289/ehp.94102s3199
|View full text |Cite
|
Sign up to set email alerts
|

Experimental localization of intestinal uptake sites for metals (Cd, Hg, Zn, Se) in vivo in mice.

Abstract: The intestinal uptake process consists of two separable steps: transport over the luminal membrane into epithelial cytoplasm and transport over the basolateral membrane into serosal fluid. A compound's residence time in mucosal epithelial cytoplasm depends on rates of the two transport processes and, if the rate of the second step is low, on the rate of mucosal sloughing. Using remitting metal isotopes, in vivo labeling profiles of the intestinal tract were obtained from mice eating their normal diet. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 40 publications
(35 reference statements)
0
7
0
2
Order By: Relevance
“…The absorption of these metals occurs predominantly in the upper intestine and can be divided into three steps: (1) a membrane transporter facilitates the transport of the metal at the brush border membrane, (2) serosal transfer to the basolateral side, and (3) basolateral transfer of the metal to the plasma. Early animal studies showed that maximal absorption of Pb15,16 and Cd17,18 also occurs in the upper intestine by a carrier‐mediated process 19,20…”
Section: Intestinal Transport Of Fe CD and Pbmentioning
confidence: 99%
“…The absorption of these metals occurs predominantly in the upper intestine and can be divided into three steps: (1) a membrane transporter facilitates the transport of the metal at the brush border membrane, (2) serosal transfer to the basolateral side, and (3) basolateral transfer of the metal to the plasma. Early animal studies showed that maximal absorption of Pb15,16 and Cd17,18 also occurs in the upper intestine by a carrier‐mediated process 19,20…”
Section: Intestinal Transport Of Fe CD and Pbmentioning
confidence: 99%
“…Understanding of the mechanisms of Cd absorption and circumventing the intestinal barrier is of prime interest. Available literature reports that, following oral exposure, Cd is absorbed in mammals preferentially in the duodenum and proximal jejunum [ 8 ]. After absorption Cd first reaches the liver.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal Cd absorption may occur either by paracellular or transcellular routes, or both. In vivo and in situ studies have shown a substantial accumulation of Cd in the intestinal tissue following oral exposure and luminal perfusion, respectively (Hoadley and Cousins, 1985;Lehman and Klaassen, 1986;Foulkes and Mc-Mullen, 1987;Andersen et al, 1994). Also, uptake experiments performed on brush-border membrane vesicles isolated from the rat and the pig small intestine have clearly demonstrated that Cd is taken up by intestinal cells (Bevan and Foulkes, 1989;Tacnet et al, 1990); thus transcellular routes seem to be involved in Cd absorption.…”
mentioning
confidence: 99%